2018
DOI: 10.5713/ajas.17.0611
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of Thai indigenous chickens based on complete sequences of mitochondrial DNA D-loop region

Abstract: ObjectiveComplete mtDNA D-loop sequences of four Thai indigenous chicken varieties, including Pra-dhu-hang-dam (PD), Leung-hang-khao (LK), Chee (CH), and Dang (DA) were explored for genetic diversity and relationships with their potential ancestor and possible associates to address chicken domestication in Thailand.MethodsA total of 220 complete mtDNA D-loop sequences of the four Thai indigenous chicken varieties were obtained by Sanger direct sequencing of polymerase chain reaction amplicons of 1,231 to 1,232… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 22 publications
5
24
1
Order By: Relevance
“…In the present study, as was previously reported in the Chilean chicken [4], haplotypes belonging to the geographically broad type E were found; this haplogroup has been identified in European animals (Plymouth Rock, White Plymouth Rock, White Leghorn, and New Hampshire), as well as in the Middle East, India, and China [45]. Regarding the haplogroup F, it is mainly concentrated in the southwest of China and in native breeds from Japan, in which Haplogroup F was reported in the Shamo breed from Okinawa [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, as was previously reported in the Chilean chicken [4], haplotypes belonging to the geographically broad type E were found; this haplogroup has been identified in European animals (Plymouth Rock, White Plymouth Rock, White Leghorn, and New Hampshire), as well as in the Middle East, India, and China [45]. Regarding the haplogroup F, it is mainly concentrated in the southwest of China and in native breeds from Japan, in which Haplogroup F was reported in the Shamo breed from Okinawa [48].…”
Section: Discussionmentioning
confidence: 99%
“…In Miao et al 5 and other reports cited in their study 18 , 19 , 23 , 32 red junglefowls (AB009432 and AB009441 in Miyake et al, 1997, direct submission to the international database GenBank [NCBI], HM462194 to HM462217 18 , D82900, D829001, and D82906 to D82908 19 ) and indigenous chicken individuals (AB007724 in Miyake et al, direct submission to the international database GenBank [NCBI]; D82922 19 ; FJ914360 and FJ914361 23 ) from Thailand were included. In addition, Teinlek et al 24 recently examined the mtDNA D-loop sequences of 220 Thai indigenous chickens consisting of four breeds (Pradu-hang-dam, Leung-hang-khao Chee, and Dang). Although Thailand may be one of the regions where chicken domestication occurred 3 , the data regarding the genetic diversity of red junglefowls and indigenous chickens in Thailand are still insufficient to accurately elucidate the origin and process of chicken domestication.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) is a critical tool for tracing evolutionary and population genetics of most domesticated animals. Also, mtDNA diversity is vital in assessing the maternal origin, phylogeny, and population structure of all domestic animals [8][9][10][11][12][13]. Previous studies of goat mtDNA (control region) revealed a total of six haplogroups (also known as lineages; A, B, and C by Luikart et al [14]; D by Sultana et al [15]; F by Sardina et al [16]; and G by Naderi et al [6]).…”
Section: Introductionmentioning
confidence: 99%